PEMBERDAYAAN LANSIA MELALUI KREASI SENI - Indro Moerdisuroso; Ataswarin Oetopo; Yufiarti Yufiarti (Bahasa Indonesia, 2018)
Abstract Empowering the Elderly through Art Creation at the Nursing Home. Improving the quality of life of the Indonesian population affects the increasing number of elderly people. For this reason, the elderly need to improve their quality of life. One solution in dealing with this situation is to empower the elderly through visual arts activities. The purpose of this community service is to empower the elderly through activities in creating art using multimedia guideline. In this activity, the target was 30 elderly residents of the Panti Sosial Tresna Werdha Bhakti Mulia 2, Cengkareng, West Jakarta. This activity uses training methods based on multimedia guidelines. This activity is held for 2 x meetings, each for 2 hours. The training process was guided by the entire community service team, accompanied by three students, and officers from the nursing home. The outputs are the guidance on creating art, and documentation of the activities. Participants showed an enthusiastic attitude in participating in training activities to create art with the topic of flora drawing. They showed a happy attitude towards the image produced. From the whole series of this activities, it was concluded that participants could understand well the training material in multimedia. The activity of drawing flora can arouse pleasure and be proud of producing a work for elderly participants. Multimedia as a learning media suitable for use for the elderly. Creative arts activities can improve the quality of life of the elderly. Abstrak Pemberdayaan Lansia Melalui Kreasi Seni. Tujuan kegiatan Pengabdian Kepada Masyarakat ini ialah untuk memberdayakan lansia melalui kegiatan berkarya seni rupa menggunakan panduan multimedia. Peningkatan kualitas hidup penduduk Indonesia berpengaruh pada meningkatnya jumlah lansia. Untuk itu lansia perlu ditingkatkan kualitas hidupnya. Salah satu solusi dalam menghadapi situasi ini adalah memberdayakan lansia melalui kegiatan seni rupa. Dalam kegiatan ini sasarannya ialah lansia warga Panti Sosial Tresna Werdha Bhakti Mulia 2, Cengkareng, Jakarta Barat berjumlah 30 orang. Kegiatan pengabdian ini menggunakan metode pelatihan berdasarkan panduan multimedia. Kegiatan ini dilaksanakan selama 2 x pertemuan, masing-masing selama 2 jam. Proses pelatihan dipandu seluruh tim PKM, didampingi tiga mahasiswa, dan petugas dari Panti Werdha. Hasil kegiatan berupa panduan berkreasi seni rupa, dan dokumentasi kegiatan berkreasi seni rupa. Peserta menunjukkan sikap antusias dalam mengikuti kegiatan pelatihan berkreasi seni dengan topik menggambar flora. Peserta menampakkan sikap senang terhadap gambar yang dihasilkan. Dari seluruh rangkaian kegiatan PKM disimpulkan bahwa peserta dapat memahami dengan baik materi dalam multimedia pelatihan yang berupa video dan buku panduan. Kegiatan kreasi seni rupa menggambar flora dapat membangkitkan rasa senang dan bangga menghasilkan suatu karya bagi peserta lansia. Multimedia sebagai media pembelajaran sesuai digunakan untuk lansia. Kegiatan kreasi seni rupa dapat meningkatkan kualitas hidup lansia.